Yogurt Favorite Level Test Using Basic Ingredients Soybean Milk With Addition of Green Spinach (Amaranthus Tricolor L.) - Kurniawan, Johannes (Jurnal Penelitian Pariwisata, 2020)
Spinach is food that is easily wilted and easily damaged, so spinach that has been harvested must be immediately marketed and consumed. There are two methods to extend the shelf life of spinach, namely cooling and drying methods. This study uses the drying method. The advantages of drying compared to cooling are that the dried material is more durable, the volume and weight are reduced, resulting in lower costs for packaging, transportation and storage. Along with the development of food technology, vegetable milk began to be introduced as an alternative ingredient for making yogurt whose nutritional value is not inferior to animal milk yogurt. In order to be more attractive to increase income and add coloring, the natural coloring is green spinach, considering there has never been researched into making yogurt with the addition of green spinach as a natural coloring. The treatment of adding green spinach vegetable extracts by 15% and 25% affects the quality changes that occur in yogurt made from soy milk. By simply differentiating the addition of 15% and 25% can prove the influence of changes in yogurt quality made from soy milk. Keywords: Organoleptic Test, Yoghurt, Green Spinach, Soy Milk